Treating a Challenging Giant Aneurysm of Middle Cerebral Artery (MCA) with a Staged Procedure of Endovascular Coiling and Flow Diverter (FD): Case Report - Mobin Ibne Mokbul; Shahidur Rahman Sikder; Md Sumon Rana; Md Motasimul Hasan; Md Shafiqul Islam (Bangladesh Journal of Neurosurgery, 2024)
Background: Giant intracranial aneurysms pose significant challenges in treatment due to a high risk of postoperative complications, including delayed rupture, cerebral edema, and aggravation of mass effect. Endovascular approaches, such as adjunctive coiling and flow diverter (FD) procedures, have become increasingly recommended for wide-necked, large, and giant aneurysms. Case Description: In this report, we present a challenging case of a staged coiling and FD procedure in a giant unruptured middle cerebral artery (MCA) aneurysm. The patient, a 26-year-old adult female, was admitted to our hospital with a history of convulsions. Digital Subtraction Angiography (DSA) revealed a massive aneurysm measuring 40 mm × 27 mm in the M1 segment of the MCA. To mitigate the risk of mass effect aggravation, we performed a two-staged procedure with a seven-day interval between the interventions. The first step involved partial endovascular coiling to shrink the aneurysm, followed by successful flow diversion. The patient did not experience further convulsions or neurologic deficits, and the follow-up angiogram showed no residual flow to the aneurysm. Conclusion: We report one of the very first cases of adjunctive coiling and FD in ‘unruptured’ giant aneurysms. Our neurovascular intervention provides valuable insights into the approach and treatment of unruptured giant aneurysms in cerebral arteries. By employing a staged procedure, effective flow diversion can be achieved even in giant unruptured aneurysms. Although further research is necessary to confirm its superiority and address critical issues, our findings may contribute to the future management of giant aneurysms and inspire avenues for research in the neurosurgical community. Bang. J Neurosurgery 2023; 12(2): 129-136